2014
DOI: 10.5653/cerm.2014.41.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in women with polycystic ovary syndrome

Abstract: ObjectiveTo investigate: the prevalence of vitamin D deficiency in Korean women with polycystic ovary syndrome (PCOS), and the relationship between vitamin D status and clinical or metabolic features in this group.MethodsWe recruited 38 women with PCOS using the Rotterdam criteria. A total of 109 premenopausal control women were matched with patients based on age and body mass index. Serum 25-hydroxy vitamin D concentrations less than 20 ng/mL were classified as frank vitamin D deficiency. Since vitamin D may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 35 publications
6
42
1
7
Order By: Relevance
“…Other studies suggest that vitamin D stimulates the expression of insulin receptors, which in turn augments insulin responsiveness for glucose transport [43,44]. Another important consideration is that the vitamin D/VDR complex regulates over 300 genes, including genes involved in glucose metabolism [45].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…Other studies suggest that vitamin D stimulates the expression of insulin receptors, which in turn augments insulin responsiveness for glucose transport [43,44]. Another important consideration is that the vitamin D/VDR complex regulates over 300 genes, including genes involved in glucose metabolism [45].…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…Our study discovered that the BMI in women with 20 Comparable outcome was also acquired by in another study in which 38 Korean women (18-40 years) were recruited with PCOS and 109 age and BMI matched non PCOS women were included. 16 Another research work was conducted in Iran by Firouzabadi et al on 100 infertile PCOS women also observed no significant association between BMI and serum vitamin D level before and after the management with vitamin D and calcium supplements. 21 Numerous studies have exhibited an inverse relationship between vitamin D and BMI in women with PCOS in the reproductive age group.…”
Section: Discussionmentioning
confidence: 94%
“…В исследованиях, предшествующих наcтоящему, средний уровень витамина D варьировал от 11 до 31 нг/мл, а в большинстве из них он не превышал 20 нг/мл [20]. В нашем исследовании он составил 21,5 нг/мл, в то время как концентрация данного ну-триента менее 30 нг/мл наблюдалась у 82,8% пациен-ток.…”
Section: Discussionunclassified
“…В нескольких исследованиях у па-циенток с СПКЯ наблюдалась связь статуса витами-на D и метаболических факторов риска, таких как ИР, дислипидемия, артериальная гипертензия, уро-вень С-реактивного белка [11,12,14]. Нами подоб-ной ассоциации выявлено не было, что согласуется с данными других исследователей [20].…”
Section: дефицит витамина D при спкяunclassified